Voice and Swallowing Disorders 2020
DOI: 10.5772/intechopen.88735
|View full text |Cite
|
Sign up to set email alerts
|

Pathology of Nonneoplastic Lesions of the Vocal Folds

Abstract: Nonneoplastic vocal fold lesions are common that can cause hoarseness and voice change. Reactive lesions of Reinke's space can be observed in all ages and genders and comprise the majority of the benign nonneoplastic vocal fold lesions. Although clinically different terms are used to define reactive lesions of Reinke's space, they share the same histopathologic features. In order to differentiate vocal fold polyp and nodule and Reinke's edema, clinical findings should be considered. Epithelial changes such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The Reinke's space is the uppermost layer of the lamina propria plica vocalis , which is composed of loosely woven collagen and elastin fibers and has an average thickness of 0.3 mm. 5,6,9,11 The number of cigarettes smoked daily and the duration of exposure to cigarette smoke correlate with clinical manifestations of RE disease. Long exposure to smoke causes higher histological damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Reinke's space is the uppermost layer of the lamina propria plica vocalis , which is composed of loosely woven collagen and elastin fibers and has an average thickness of 0.3 mm. 5,6,9,11 The number of cigarettes smoked daily and the duration of exposure to cigarette smoke correlate with clinical manifestations of RE disease. Long exposure to smoke causes higher histological damage.…”
Section: Discussionmentioning
confidence: 99%
“…Long exposure to smoke causes higher histological damage. 11,12 However, research by Tavaluc et al showed a weak correlation between the increase in cigarette use per pack and the severity of RE. Although exposure to tobacco can affect the development of RE, this study shows that more than just tobacco causes an increase in RE.…”
Section: Discussionmentioning
confidence: 99%
“…Gender on its side has shown to be a more important issue in voice pathology. Women are more prone to suffer from vocal fold diseases like Reinke's edema because of their vocal fold structure [52], but gender aspects also influence the acoustical feature values obtained in signal analysis [53]. This might explain the differences in feature selection among databases: although sex is never selected as a good predictor, the proportion of male/female subjects in both healthy and pathological recordings varies throughout databases.…”
Section: Discussionmentioning
confidence: 99%
“… 23 Prolonged vocal abuse results in repetitive injuries to the laryngeal mucosa, which may lead to benign inflammatory lesions of the vocal cords. 23 24 Many studies 25 26 27 28 have reported that the prevalence of hyperfunctional voice disorders is higher in individuals with a history of vocal abuse.…”
Section: Introductionmentioning
confidence: 99%